Small RNAs in Outer Membrane Vesicles and Their Function in Host-Microbe Interactions - Ahmadi Badi, Sara; Bruno, Stefania Paola; Moshiri, Arfa; Tarashi, Samira; Siadat, Seyed Davar; Masotti, Andrea (Frontiers in Microbiology, 2020)
Outer membrane vesicles (OMVs) produced by Gram-negative bacteria and their RNA content have recently received increasing attention as novel mediators of host-guest intercellular and interspecies communication. These kind of vesicles allows not only the export of proteins but also of nucleic acids and small RNAs. We previously reported that the production of bacterial vesicles able to communicate with the surrounding environment can be a general mechanism, exploited by bacteria but also by viruses, to convey “messages” able to modulate the physiological activity and the gene expression of cells and tissues (without inducing cell toxicity), ultimately leading to the manipulation of the host immune response. Many functions attributed to OMVs are a consequence of their high capability to survive to different environmental stressors and to enter into cells quite easily. As these properties can be exploited to advantage human health, in this review we summarized the papers that reported the use of OMVs as modulators of cellular activities through the involvement of the RNAs contained within. We also discussed what have been done with OMVs and what remains to be discovered in order to prompt the investigations toward the complete elucidation of the role and functions of these vesicles.